2013
DOI: 10.1136/annrheumdis-2013-204494
|View full text |Cite
|
Sign up to set email alerts
|

Circulating C reactive protein in osteoarthritis: a systematic review and meta-analysis

Abstract: Low-grade systemic inflammation may play a greater role in symptoms rather than radiographic changes in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
147
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(170 citation statements)
references
References 44 publications
8
147
1
Order By: Relevance
“…Many cohort studies have , making further investigation into this link necessary. A meta-analysis of 32 reported clinical studies by Jin and colleagues further complicates the role of CRP in OA pathogenesis, as it was concluded that lowgrade systemic inflammation may play a more prominent role in symptoms of OA 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Many cohort studies have , making further investigation into this link necessary. A meta-analysis of 32 reported clinical studies by Jin and colleagues further complicates the role of CRP in OA pathogenesis, as it was concluded that lowgrade systemic inflammation may play a more prominent role in symptoms of OA 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans with OA, serum CRP typically ranges from 3,000 to 8,000 μg/L [42]. Several dogs in the present study had serum CRP values >8,000 μg/L, suggesting more severe joint inflammation and greater risk of disease progression [43]. We also found that synovial/serum CRP ratio in partial CR stifles was correlated with progressive CrCL fiber tearing, supporting the concept that CRP reflects severity and progression of synovitis/OA [44,45] and, additionally, non-contact complete CR in dogs.…”
Section: Discussionmentioning
confidence: 98%
“…While the effect size for CRP was small (Cohen’s d = 0.2), it is interesting to note that the variance in serum levels was relatively small (range 1 to 20 mg/l), which suggests that even small variations in CRP are associated with higher levels of preoperative pain. In a recent systematic review that evaluated for associations between serum levels of CRP and pain, function, and radiographic changes in OA patients compared to healthy controls [22], weak but significant correlations were found between higher CRP levels and higher pain scores as well as decreases in physical function. No correlation was found between CRP levels and radiographic changes, which suggest that low grade systemic inflammation may play a role in patients’ symptom experiences but not in cartilage deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine was included in this analysis because patients with higher levels of creatinine (i.e., males >105, females >90) did not receive celecoxib, which may have led to higher postoperative pain. Higher levels of C-reactive protein and obesity are associated with higher levels of pain in patients with OA but the impact on postoperative pain is not known [22]. Lower resting blood pressure levels are been associated with lower acute pain thresholds [23].…”
Section: Methodsmentioning
confidence: 99%